Resistência ao cisalhamento de diferentes sistemas adesivos no esmalte dental - Paradella, Thaís Cachuté [UNESP] (2005)
The purpose of this study was to evaluate in vitro three adhesive systems: a total etch single-component (GI Prime & Bond 2.1 ), a self-etching primer (GII Clearfil SE Bond) and a self-etching adhesive (GIII One Up Bond F), through shear bond strength on enamel of human teeth, evaluating the type of fracture through stereomicroscopy. Thirty premolars, kept in 0.5% chloramines solution received cuts in mesium-distal sense and had their ena mel surfaces prepared. They were randomly assigned to three experimental groups (n=20). The adhesive system's area of acting was determined and the adhesive procedures were performed according to the manufactureis instructions. 3mm Z-250 composite resin cylinders were performed. The specimens were kept in distilled water at 370C for 24h, thermocycled for 500 cycles (5ºC-55ºC) and submitted to shear with 0.5mm/min speed. The adhesive resistance mediums were GI 18.13 ± 6.49 MPa, with 55% of resin cohesive fractures; GII 17.12 ± 5.80 MPa with 90% of adhesive fractures and GIII 10.47 ± 3.14 MPa with 85% of adhesive fractures. The data was submitted to Anova and Tukey multiple comparison (5%) statistical analysis. There were no significant differences between Gl and GIl, having GIII significant difference regarding the other groups. The predominant type of fracture (adhesive in GIl) was submitted to SEM and the rupture in the resin-tooth interface was noticeable. lt was concluded that the adhesive system in Gl presented similar shear bond strength to GIl, however with a different type of fracture